DAMPAK PANDEMI COVID-19 TERHADAP KINERJA UMK BEEBEEBLESS COLLECTION DI AIRMADIDI KABUPATEN MINAHASA UTARA - LENGKONG, JULIO RONALDO TOGAS; TUMBEL, TINNEKE MEISKE; MUKUAN, DANNY DAVID SAMUEL (Sam Ratulangi University, 2020)
The study titled the impact of the Covid 19 pandemic on the performance of the BeebeeblesCollection UMK in Airmadidi, North Minahasa Regency. The research objective was to determine theimpact of the Covid 19 pandemic on the performance of the Beebeebles Collection UMK in Airmadidi,North Minahasa Regency.The results showed that The negative implications due to the Covid 19 pandemic began to hitthe Beebeebless Micro business since March 2020. The company began to experience a significant declinein performance where the company's turnover decreased by 20%. In September - November 2020, thecompany's performance declined by 70%. The Beebeebles Collection as part of Small and MediumBusiness actors actually experiences direct impact due to the Covid 19 pandemic so that the company'sperformance has decreased sharply which is marked by a decrease in turnover of up to 70%. BeebeeblesCompany must maintain good business tips that have survived the crisis of the Covid 19 pandemic. Thesetips should be maintained and developed continuously for the existence and progress of the BeebeeblesCollection company.Keywords: Impact, Covid-19, Performance, UMK